TQM-A Need in Engineering Education - Dhavale, Sunita Vikrant; Khanuja, Harmeet Kaur (Journal of Engineering Education Transformations, 2009)
Total Quality Management (TQM) is a philosophy and system for continuously improving the services and/or products offered to customers. The advantages of TQM have been valued by many companies around the world. Many organizations have achieved excellence and competitive lead by putting into practice TQM policy. Most of the principles of TQM can advantageously be employed in the area of education and training. This paper highlights the need of TQM in engineering educational institutions and explains how they can improve the quality of their services by implementing principles of TQM.